Construction of a stable periodic solution to a semilinear heat equation with a prescribed profile. (January 2016) - Mahmoudi, Fethi; Nouaili, Nejla; Zaag, Hatem
Abstract: We construct a periodic solution to the semilinear heat equation with power nonlinearity, in one space dimension, which blows up in finite time T only at one blow-up point. We also give a sharp description of its blow-up profile. The proof relies on the reduction of the problem to a finite dimensional one and the use of index theory to conclude. Thanks to the geometrical interpretation of the finite-dimensional parameters in terms of the blow-up time and blow-up point, we derive the stability of the constructed solution with respect to initial data.